Enzyme inhibition and antibacterial potential of 4-Hydroxycoumarin derivatives (Brazilian Journal of Pharmaceutical Sciences, 2021)
The 4-Hydroxycoumarin derivatives are known to show a broad spectrum of pharmacological applications. In this paper we are reporting the synthesis of a new series of 4-Hydroxycoumarin derivatives synthesized through Knovenegal condensation; they were characterized by using UV-Vis, FT-IR, NMR spectroscopies. The synthesized compounds were evaluated for antibacterial activity against Staphylococcus aureus and Salmonella typhimurium strains. The compounds (2), (3) and (8) showed favorable antibacterial activity with zone of inhibitions 26.5± 0.84, 26.0 ± 0.56 and 26.0 ± 0.26 against Staphylococcus aureus (Gram-positive) respectively. However, the compounds (5) and (9) were found more active with 19.5 ± 0.59 and 19.5 ± 0.32 zone of inhibitions against Salmonella typhimurium (Gram-negative). Whereas, in urease inhibition assay, none of the synthesized derivatives showed significant anti-urease activity; although, in carbonic anhydrase-II inhibition assay, the compound (2) and (6) showed enzyme inhibition activity with IC50 values 263±0.3 and 456±0.1, respectively.